2010
DOI: 10.1007/s12028-010-9405-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Critical Care Skills Training Using a Human Patient Simulator

Abstract: Neurosurgical critical care education is important for safe and effective care for patients. Clinical experience and didactic lectures help trainees obtain a solid knowledge base, but do not provide the benefit for learning in a fail-safe environment. Through the use of HPS, we have enhanced the critical care education of our trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 15 publications
0
21
0
2
Order By: Relevance
“…In one instance, critical care scenarios were simulated as opposed to a specific surgical procedure. 36 The commonest simulator used was ImmersiveTouch (n = 7; 25%), followed by the Procedicus Vascular Intervention System Training (VIST; Mentice AB) (n = 4; 14%) and the in vivo rat model (n = 3; 11%). Table 3 shows the different types of procedures simulated using the different surgical models.…”
Section: Characteristics Of Included Studies and Study Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one instance, critical care scenarios were simulated as opposed to a specific surgical procedure. 36 The commonest simulator used was ImmersiveTouch (n = 7; 25%), followed by the Procedicus Vascular Intervention System Training (VIST; Mentice AB) (n = 4; 14%) and the in vivo rat model (n = 3; 11%). Table 3 shows the different types of procedures simulated using the different surgical models.…”
Section: Characteristics Of Included Studies and Study Settingsmentioning
confidence: 99%
“…Training of medical students and residents from several specialties in various neurocritical care scenarios using the Human Patient Simulator improved knowledge-based written assessment scores. 36 Table 6 shows the variety of assessment tools used in the reviewed studies, which comprised the following 3 broad categories: 1) subjective evaluation or feedback surveys; 2) performance at a surgical task assessed either by a rater 10,39 (including self-rating 56 ), simulator-derived metrics, 5,6,[26][27][28][29][30]38,47,57 or both; 9,12,13,18,52 and 3) knowledge-based written tests. 11,12,36 Therefore, a significant number of studies reported participant feedback without objective evidence for efficacy of the simulator.…”
mentioning
confidence: 99%
“…[11][12][13] Simulation-based interventions in the ICU setting have also shown promise in promoting resident confidence 14 and critical care skills. 15 Information regarding skill transfer from the simulated setting to the bedside is limited. However, 1 study showed residents who received simulation-based education performed better on an ICU bedside clinical skills examination than residents who received traditional clinical training alone.…”
Section: Introductionmentioning
confidence: 99%
“…Mussacchio et al [7] developed advanced simulation models for training in the field of neurosurgery (spinal shock, closed head injury, and cerebral vasospasm). They pointed out that while traditional lectures can provide a ''solid knowledge base'', simulation in a protected environment allows the consolidation of this knowledge that is necessary in order to ensure safe and effective interventions in the field.…”
Section: Simulation Models In Neurosciencementioning
confidence: 99%